Development of the strain–rate and temperature sensitive theory of microstrain - Онищенко, Инна Сергеевна; Черняков, Юрий Абрамович; Шнейдер, Владимир Петрович (Eastern-European Journal of Enterprise Technologies, 2015)
Plastic flow, caused by the dislocation glide is closely related to the thermal activation mechanism in a wide range of strain rates. On the other hand, the high-rate plastic strain may lead to an apparent increase in temperature. Therefore, the influence of strain rate and temperature are usually related and should be considered both in the study of the materials behavior, depending on the strain rate. Over the past three decades, this approach has been implemented in a number of the continuum and physical theories of thermoviscoelasticity that lead to rather complicated constitutive relations and their use is restricted mainly by simple loading processes. A generalized version of the theory of microstrain, which is sufficiently simple and suitable to describe the finite visco-plastic strain in a wide range of strain rates and temperatures was proposed. Constitutive relations of the theory that are applicable not only under simple, but also complex loading were built. The algorithm for their numerical implementation, which allows to take into account not only the plurality of active microplastic strains but also possibility to set an arbitrary loading trajectory was proposed. A comparison of the charts of uniaxial tension at various strain rates obtained using the theory of microstrain with the known experimental data was performed. It is shown that the proposed option allows to achieve a satisfactory description of experiments with a small number of material constants, which simplifies the calibration of the theory. The results significantly extend the capabilities of the theory of microstrain and open up prospects for its use to describe the viscoplastic flow and solve applied tasks under complex loading.